Estimating glomerular filtration rate for the full age spectrum from serum creatinine and cystatin C - Pottel, Hans; Delanaye, Pierre; Schaeffner, Elke; Dubourg, Laurence; Eriksen, Bjørn Odvar; Melsom, Toralf; Lamb, Edmund J.; Rule, Andrew D.; Turner, Stephen T.; Glassock, Richard J.; De Souza, Vandréa; Selistre, Luciano; et al. (Nephrology, dialysis, transplantation, 2017)
We recently published and validated the new serum creatinine (Scr)-based full-age-spectrum equation (FAS crea ) for estimating the glomerular filtration rate (GFR) for healthy and kidney-diseased subjects of all ages. The equation was based on the concept of normalized Scr and shows equivalent to superior prediction performance to the currently recommended equations for children, adolescents, adults and older adults. Based on an evaluation of the serum cystatin C (ScysC) distribution, we defined normalization constants for ScysC ( Q cysC  =   0.82 mg/L for ages <70 years and Q cysC  =   0.95 mg/L for ages ≥70 years). By replacing Scr/ Q crea in the FAS crea equation with ScysC/ Q cysC , or with the average of both normalized biomarkers, we obtained new ScysC-based (FAS cysC ) and combined Scr-/ScysC-based FAS equations (FAS combi ). To validate the new FAS cysC and FAS combi we collected data on measured GFR, Scr, ScysC, age, gender, height and weight from 11 different cohorts including n  = 6132 unique white subjects (368 children, aged ≤18 years, 4295 adults and 1469 older adults, aged ≥70 years). In children and adolescents, the new FAS cysC equation showed significantly better performance [percentage of patients within 30% of mGFR (P30) = 86.1%] than the Caucasian Asian Paediatric Adult Cohort equation (P30 = 76.6%; P < 0.0001), or the ScysC-based Schwartz equation (P30 = 68.8%; P < 0.0001) and the FAS combi equation outperformed all equations with P30 = 92.1% (P < 0.0001). In adults, the FAS cysC equation (P30 = 82.6%) performed equally as well as the Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI cysC ) (P30 = 80.4%) and the FAS combi equation (P30 = 89.9%) was also equal to the combined CKD-EPI equation (P30 = 88.2%). In older adults, FAS cysC was superior (P30 = 88.2%) to CKD-EPI cysC (P30 = 84.4%; P < 0.0001) and the FAS combi equation (P30 = 91.2%) showed significantly higher performance than the combined CKD-EPI equation (P30 = 85.6%) (P < 0.0001). The FAS equation is not only applicable to all ages, but also for all recommended renal biomarkers and their combinations.